In the mind's eye : multidisciplinary approaches to the evolution of human cognition - Nowell, April, 1969- (Archaeological series (Ann Arbor, Mich.), 2001)
The last decade has witnessed a sophistication and proliferation in the number of studies focused on the evolution of human cognition, reflecting a renewed interest in the evolution of the human mind in anthropology and in many other disciplines. The complexity and enormity of this topic requires the coordinated efforts of many researchers. This volume brings together the disciplines of palaeontology, psychology, anatomy, and primatology. Together, they address a number of issues, including the evolution of sex differences in spatial cognition, the role of archaeology in the cognitive sciences, the relationships between brain size, cranial reorganization and hominid cognition, and the role of language and information processing in human evolution.